RIVER HISTORIOGRAPHY IN THE WORKS OF SOUTH KALIMANTAN PAINTS 1950-2000 - Putri Dyah Indriyani; Wisnu Subroto (Universitas Lambung Mangkurat, 2022)
The life of the river community in South Kalimantan with the dynamics that surround it over time has undergone a cultural transformation. The cultural transformation that is sometimes so fast makes the orientation of the people change too. These changes are recorded and illustrated in the works of painters from South Kalimantan through scratches on canvas. This research has the aim of being an inventory as well as an insight into the meaning behind river paintings in South Kalimantan as a representation of past communities. The historical method is used to explore data and facts from events left by historical actors, both in the form of writing, paintings, and relics that they have used. Changes in the people of South Kalimantan can be seen or traced through historical research. The results of this study can clearly describe the social reality and beauty of the river communities in South Kalimantan which have changed through the painter's strokes in pictures from time to time. This reality can provide a new understanding of painting as an aesthetic portrait of the traces of the past. Thus, river painting in South Kalimantan can be viewed from various aspects, one of which is through its historiography.